2017
DOI: 10.1007/s11605-017-3405-2
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Reconstruction Technique During Pancreaticoduodenectomy After Roux-En-Y Gastric Bypass: How I do It

Abstract: The altered anatomy in patients after bariatric surgery who have undergone a Roux-en-Y gastric bypass may pose a technical challenge for surgical removal of the pancreatic head. We treat patients with pancreas cancer with multimodality therapy in a neoadjuvant fashion followed by pancreaticoduodenectomy (PD). In patients with Roux-en-Y gastric bypass anatomy, the gastric remnant is preserved and used for pancreaticogastrostomy reconstruction and subsequently drained by the same jejunal limb used for the hepati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Another possible way to utilize the remnant stomach is for reconstruction. Younan et al described a method in which the gastric remnant is preserved and used for pancreaticogastrostomy (PG) reconstruction and subsequently drained by the same jejunal limb used for the HJ (17). Tsamalaidze et al reported that out of seven patients with stomach preservation, the remnant stomach was used for pancreatic reconstruction in three patients and two patients had insertion of transgastric jejunal feeding tube for nutrition (18).…”
Section: Discussionmentioning
confidence: 99%
“…Another possible way to utilize the remnant stomach is for reconstruction. Younan et al described a method in which the gastric remnant is preserved and used for pancreaticogastrostomy (PG) reconstruction and subsequently drained by the same jejunal limb used for the HJ (17). Tsamalaidze et al reported that out of seven patients with stomach preservation, the remnant stomach was used for pancreatic reconstruction in three patients and two patients had insertion of transgastric jejunal feeding tube for nutrition (18).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, with both the increasing incidence of pancreatic cancer and number of patients undergoing bariatric procedures, this clinical scenario will become more prevalent, making discussions of the surgical options more frequent and relevant. Furthermore, gastric remnant preservation, while currently performed less frequently, may be advantageous from a multidisciplinary standpoint, but clearly requires further investigation [ 61 ]. Although not discussed, decisions regarding preoperative diagnostic modalities or perioperative neoadjuvant and adjuvant treatments for this unique, but expanding, patient population deserves further review.…”
Section: Discussionmentioning
confidence: 99%